2022
DOI: 10.3389/fonc.2022.857148
|View full text |Cite
|
Sign up to set email alerts
|

Search for Key Genes and Functional Pathways of Ulcerative Colitis to Colon Cancer Based on Bioinformatics

Abstract: Ulcerative colitis (UC) is a persistent and diffuse inflammatory disease of the intestine. It is widely prevalent in developed countries. Approximately 30% of patients with UC suffer from widespread and aggressive colitis and are at increased risk of colon cancer. In this study, the genetic features and potential molecular mechanisms shared between UC and colorectal cancer were investigated. The datasets from GEO and TCGA were analyzed to obtain differentially expressed genes, of which there were 116 overlappi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The NF-κB pathway has long been recognized as a classic proinflammatory signaling pathway. Increased NF-B activity indirectly encourages the development of neutrophil extracellular traps (NET), one of neutrophils' antimicrobial defense mechanisms [49]. It has been demonstrated that Sirtuin 1 (SIRT1) binds to HSF1 and controls the acetylation status of HSF1 to act as a regulator of HSF1 DNA-binding activity [50].…”
Section: Resultsmentioning
confidence: 99%
“…The NF-κB pathway has long been recognized as a classic proinflammatory signaling pathway. Increased NF-B activity indirectly encourages the development of neutrophil extracellular traps (NET), one of neutrophils' antimicrobial defense mechanisms [49]. It has been demonstrated that Sirtuin 1 (SIRT1) binds to HSF1 and controls the acetylation status of HSF1 to act as a regulator of HSF1 DNA-binding activity [50].…”
Section: Resultsmentioning
confidence: 99%
“…WGCNA is a powerful tool that identifies highly collaborative gene sets and helps to discover candidate biomarkers and therapeutic targets for cancer. Besides, it helps to discover biologically significant co-expressed gene modules by analyzing the interconnectivity of gene sets and their association with phenotypes, and to study the relationship between gene networks and disease [ 14 ]. In this investigation, CAH-B-, LC- and HCC-related gene modules were analyzed using WGCNA.…”
Section: Methodsmentioning
confidence: 99%
“…In gallbladder cancer, positive CCT2 expression was negatively correlated with low postoperative patient survival and positively correlated with high mortality ( 10 ). In our previous study, we found that CCT2 expression showed an increasing trend in normal, ulcerative colitis, and colon cancer tissues by analyzing data from The Cancer Genome Atlas (TCGA) database and Gene Expression Omnibus (GEO) database and predicted the possibility that CCT2 may be closely associated with the development of colon inflammation or cancer and that CCT2 is a prognostic factor for colon cancer ( 11 ). Therefore, a combination of previous studies and our previous study started from CCT2 and cited the clinical data of various human cancers, genomic variants, mRNA expression, miRNA expression, methylation, and other data included in TCGA database as well as protein expression in different human tissues and organs included in the Human Protein Atlas (HPA) database in order to explore the function of the role CCT2 plays in various cancers.…”
Section: Introductionmentioning
confidence: 99%